2019
DOI: 10.24985/kjss.2019.30.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Korean Life Skills Scale for Sport (KLSSS)

Abstract: Purpose The purpose of this study was to develop a Korean Life Skills Scale for Sports (KLSSS) that original version is the LSSS developed by Cronin and Allen (2017). Methods The subjects were 899 middle school and high school students. The measurement tool was used with LSSS. The validation of KLSSS followed a three-stage of validation procedure; substantive stage, structural stage, and external stage. The result is as follows. Results First, In the substantive stage, KLSSS consisted of 47 items with 8 factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
3
5
0
Order By: Relevance
“…Consistent with previous findings ( AÇAK and DÜZ, 2018 ; Lim et al, 2019 ), some re-specification of the original LSSS model suggested by Cronin and Allen (2018) was needed for the scale to fit within the current cultural context. While the revised version of the scale consists of the original eight factors ( Cronin and Allen, 2017 ; Teamwork, Goal setting, Social skills, Problem solving and decision making, Emotional skills, Leadership, Time management, and Interpersonal communication), only 34 items from the original scale were retained within this study.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Consistent with previous findings ( AÇAK and DÜZ, 2018 ; Lim et al, 2019 ), some re-specification of the original LSSS model suggested by Cronin and Allen (2018) was needed for the scale to fit within the current cultural context. While the revised version of the scale consists of the original eight factors ( Cronin and Allen, 2017 ; Teamwork, Goal setting, Social skills, Problem solving and decision making, Emotional skills, Leadership, Time management, and Interpersonal communication), only 34 items from the original scale were retained within this study.…”
Section: Discussionsupporting
confidence: 83%
“…The LSSS was developed with the aim of creating a sport-specific measure of like skills development. While scores produced by the LSSS were found to be reliable and valid among samples of British youth sport participants ( Cronin and Allen, 2017 , 2018 ; Mossman and Cronin, 2019 ), only four known studies have examined the scale’s psychometric properties within other cultural contexts ( AÇAK and DÜZ, 2018 ; Lim et al, 2019 ; Nascimento-Junior et al, 2020 ; Sabourin et al, 2020 ). With evidence of a growing interest in sport-based PYD programs across the African continent, research examining the reliability and validity of scores derived from existing measures of life skills, within this context, is highly needed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations